2016
DOI: 10.3823/1891
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS and seniors: knowledge of the elderly about the disease

Abstract: Introduction: The spread of HIV/AIDS in the elderly population is already characterized as a serious public health problem, requiring the development of actions and strategies to reduce the vulnerability of these individuals. Objective: Identifying the knowledge of older people about HIV/ AIDS. Method: This is an exploratory-descriptive study of a qualitative approach, developed with 26 elderly enrolled in three Family Health Strategies of the city of Cajazeiras, Paraiba, Brazil. Data were collected through in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
1
3
0
3
Order By: Relevance
“…In this study, 87% of the sample (n = 21) reported knowing the means of transmission of HIV/ AIDs, with the use of condoms as the main means of prevention and corroborating with other studies that state that condoms are the best known prevention of HIV/AIDS for the elderly and that is used less for them compared to younger people, limiting their use only in sex with strangers or in cases of suspicion of partner loyalty [6,7,8,9] It is important to note that the statistical data from epidemiological bulletin HIV/AIDs the Ministry of Health showed that married heterosexual women or stable union has been a risk group in the acquisition of this epidemic [2], because this type of relationship brings a "false" security And trust for the woman because it is a single partner, generating an inappropriate behavior in the prevention of high risk. A major difficulty in sex education permeates in negotiating condom use with partners, the pejorative sense of the possibility of marital infidelity [15].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In this study, 87% of the sample (n = 21) reported knowing the means of transmission of HIV/ AIDs, with the use of condoms as the main means of prevention and corroborating with other studies that state that condoms are the best known prevention of HIV/AIDS for the elderly and that is used less for them compared to younger people, limiting their use only in sex with strangers or in cases of suspicion of partner loyalty [6,7,8,9] It is important to note that the statistical data from epidemiological bulletin HIV/AIDs the Ministry of Health showed that married heterosexual women or stable union has been a risk group in the acquisition of this epidemic [2], because this type of relationship brings a "false" security And trust for the woman because it is a single partner, generating an inappropriate behavior in the prevention of high risk. A major difficulty in sex education permeates in negotiating condom use with partners, the pejorative sense of the possibility of marital infidelity [15].…”
Section: Resultssupporting
confidence: 61%
“…It is therefore important that the elderly acquire knowledge about the pathology and the means of transmission, as well as, be aware of the safe practice of sexual activity, the use of condoms and the handling of syringes in blood transfusion or injectable drugs, as actions to identify risky behavior [4,6,7,8].…”
Section: Theoretical Referencementioning
confidence: 99%
“…10,19 Embora tenha sido observado que a maioria dos idosos entrevistados possuía baixos níveis educacionais, a renda mensal da maior parte dos que sofreram quedas e do total de entrevistados variava entre três e cinco salários mínimos, algo que diverge dos achados de outros estudos, em que a queda é mais presente em indivíduos com baixo poder socioeconômico, podendo estar relacionado ao pouco acesso aos recursos médicos e reduzido conhecimento sobre as formas de prevenir as alterações corporais e fatores de risco para as quedas. 20,21 Foi evidenciada associação estatisticamente significante (p≤0,05) entre a não utilização de dispositivo para auxílio da marcha e quedas.…”
Section: Resultsunclassified
“…This finding is relevant because it points to a representational change in the central system, as it evidences an attempt to overcome the representation of immediate death by the syndrome, seeking strategies to cope with its condition in an attempt to adapt to the current context of life and health (15) . Thus, the representation of AIDS brings to the fore the idea of prevention, however, there are still practices and risk behaviors, such as not using condoms in a relationship based on trust and strong bonds of affection (16) . Also, the non-sharing of objects and the need to know the partner with whom they relate are the most used prevention strategies used by the female prison population (6) .…”
Section: Discussionmentioning
confidence: 99%
“…Social stigma affects the quality of life of women, especially in situations of deprivation of liberty. Therefore, it is necessary to rethink ways of combating these aspects of the repercussion of the disease that are present in the social representations of AIDS, which are responsible for disseminating frightening meanings in relation to the epidemic, negatively influencing the implementation of actions and strategies for preventing and controlling this injury (15)(16) .…”
Section: Discussionmentioning
confidence: 99%